2020
DOI: 10.21203/rs.3.rs-56279/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mTOR-dependent dysregulation of autophagy contributes to the retinal ganglion cell loss in streptozotocin-induced diabetic retinopathy

Abstract: Background: Neurodegeneration, an early event in the pathogenesis of diabetic retinopathy (DR), precedes clinically detectable microvascular damage. Autophagy dysregulation is considered a potential cause of neuronal cell loss, however underlying mechanisms remain unclear. The mechanistic target of rapamycin (mTOR) integrates diverse environmental signals to coordinate biological processes, including autophagy. Here, we investigated the role of mTOR signaling in neuronal cell death in diabetic retinopathy. Met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(57 reference statements)
1
1
0
Order By: Relevance
“…Several studies show that the mTOR signaling pathway is involved in miR-155-mediated regulation (16,22). In addition, mTOR contributes to glaucoma development and is associated with RGC activity (13,32,33). Here, we found that the expression of mTOR was downregulated in H 2 O 2treated RGCs.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Several studies show that the mTOR signaling pathway is involved in miR-155-mediated regulation (16,22). In addition, mTOR contributes to glaucoma development and is associated with RGC activity (13,32,33). Here, we found that the expression of mTOR was downregulated in H 2 O 2treated RGCs.…”
Section: Discussionsupporting
confidence: 51%
“…It is recognized that the mTOR signaling pathway contributes to the activation of RGCs (13,14). In addition, mounting evidence demonstrates that miR-155 can modulate pathological states including cardiomyopathy (15), cancer (16), and alcoholic liver disease (17) via targeting the mTOR signaling pathway.…”
Section: Micrornas (Mirnas) Are a Class Of Conserved Smallmentioning
confidence: 99%